Phenylethylchromones with In Vitro Antitumor Promoting Activity from Aquilaria filaria - Suzuki, Airi; Miyake, Katsunori; Saito, Yohei; Rasyid, Faradiba Abdul; Tokuda, Harukuni; Takeuchi, Misa; Suzuki, Nobutaka; Ichiishi, Eiichiro; Fujie, Tetsuo; Goto, Masuo; Sasaki, Yohei; Nakagawa-Goto, Kyoko (Planta Medica, 2017)
A new chromone, 2-(2-hydroxy-2-phenylethyl)chromone (1), was isolated together with ten known phenylethyl chromones from MeOH extracts of agarwood (Aquilaria filaria). The selected compounds were evaluated in an antiproliferative assay against five human tumor cell lines, including a multidrug-resistant cell line. They were also tested for antitumor promoting activity, as mediated by 12-O-tetradecanoylphorbol-13-acetate-induced activation of the Epstein-Barr virus early antigen in Raji cells. Among all compounds, 4′,7-dimethyoxy-6-hydroxychromone (2) displayed broad spectrum antiproliferative activity against all tumor cell lines tested with IC50 values of 25–38 µM, while 8 was selectively inhibitory against multidrug-resistant cells. All tested compounds suppressed tumor promotion at noncytotoxic concentrations. 4′,6-Dihydroxyphenylethylchromone (7) exhibited the most potent effect with an IC50 value of 319 mol ratio relative to 12-O-tetradecanoylphorbol-13-acetate. This study is the first to report the antitumor promoting activity of 2-(2-phenylethyl)chromone derivatives, as well as the selective antiproliferative activity of 8 against a multidrug-resistant tumor cell line.
Keywords: agarwood; Aquilaria filaria (Oken) Merr.; Thymelaeaceae; 2-(2-phenylethyl)chromone; antitumor promoting activity; antiproliferative activity